A Technique to Improve Ridge Flows of Fingerprint Orientation Fields Estimation - Saparudin Saparudin; Ghazali Sulong (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexAn accurate estimated fingerprint orientation fields is a significant step for detection of singular points. Gradient-based methods are frequently used for estimating orientation fields but those methods are sensitive to noise. Fingerprints that perfect quality are seldom. They may be corrupted and degraded due to impression conditions or variations on skin. Enhancement of ridge flows improved the structure of orientation fields and hence increased the number of true singular points thereby conducting the overall performance of the classification process. In this paper, we provided discussion on the technique and implementation to improve local ridge flows segmentation; secondly, identification of noise areas and marking; thirdly, estimation of fingerprint orientation fields using gradient-based method and finally, enhancement of ridge flows using minimum variance of the cross centre block direction in squared gradients. A standard fingerprint database is used for testing of proposed technique to verify the tier of effectivity of algorithm. The experimental results suggest that our enhanced algorithm achieves visibly better ridge flows compare to other methods.